Two new species of Hoplonannus (Heteroptera: Schizopteridae: Schizopterinae) from the Brazilian Amazon - Almeida, Flavio Roberto De Albuquerque; Carvalho-Filho, Fernando Da Silva; Castro, Heitor Antunes De; Fernandes, Jose Antonio Marin (Zootaxa, 2019)
The genus Hoplonannus McAtee & Malloch, 1925 is composed of H. brunneus, H. paenebrunneus, H. craneae, and H. australis, all previously recorded from Central and South America. In this paper, we describe Hoplonannus bifidus sp.n. and Hoplonannus robustus sp.n. based on several specimens collected in the Brazilian Amazon, representing the first record of the genus from northern Brazil. We provide diagnoses, photographs of habitus, scanning electron micrographs of male genitalia, and illustrations of female genitalia. A key to species based on males of Hoplonannus is also presented.